Efficient waste polyvinyl(butyral) and cellulose composite enabled carbon nanofibers for oxygen reduction reaction and water remediation - Park, Jong Chel; Kim, Jae-Chan; Park, Sangbaek; Kim, Dong-Wan (ELSEVIER, 2020)
Waste polyvinyl(butyral) (W-PVB) collected from the windshields of end-of-life vehicles has drawn considerable interest as a complementary and abundant resource. However, large amounts of W-PVB are still being buried in landfills every year owing to a lack of recycling techniques. As an alternative, we report the fabrication of carbon nanofibers from natural cellulose and W-PVB composites using a facile electrospinning, carbonization, and KOH activation approach. Interestingly, volatiles and residual carbon from a W-PVB matrix through carbonization produce highly porous carbon nanofibers and a defective graphitic surface layer, respectively. As a result of the large surface area (698.1 m(2) g(-1)) and pore volume (0.2919 cm(3) g(-1)) from abundant micropores, as well as the high density of active sites from defects, resulting carbon nanofiber shows a superior performance in environmental applications. It serves as a metal-free and un-doped carbon catalyst with a half-wave potential of 0.76 V vs RHE for the oxygen reduction reaction and a 99.6% removal of rhodamine B from water as an adsorbent for water remediation. This simple strategy can open a new approach to the design and synthesis of various classes of W-PVB-based composites, which will broaden the reuse of W-PVB in renewable and sustainable applications.
Keywords: BACTERIAL CELLULOSE; ELECTROCATALYST; DEPOSITION; CATALYSTS; GLASS